Marketing and Social Media Management in Healthcare: A Bibliometric Analysis (2015-2024) - Yilmaz, Faruk (Ege Univ, Fac Economics & Admin Sciences, 2026)
This study presents a bibliometric analysis of peer-reviewed articles from the Web of Science (2015-2024) to examine the evolution of marketing and social media management in healthcare. Three search strategies topic-based, title-focused, and T & uuml;rkiye-specific identify publication trends, collaboration networks, and thematic shifts. Results indicate a 16.44% annual growth in publications, driven by digital transformation and pandemic-related studies.The United States, the United Kingdom, and China lead in research output, while T & uuml;rkiye, despite ranking among the top 20 contributors and increasing its academic engagement, shows limited international collaboration (6.5%). Topic-based searches emphasize social media, COVID-19, and public health,while refined searches highlight marketing, branding, health communication, and patient satisfaction. Twitter, Facebook,and YouTubeplay key roles in patient engagement and information dissemination. By mapping thematic shifts, this study uncovers global trends, regional collaborations, and also includes a country-level perspective by examining T & uuml;rkiye as a case example, underscoring the evolving role of social media and communication strategies in healthcare marketing.
Keywords: Healthcare Marketing; Social Media; Bibliometric Analysis